(untitled) (Academia Science Repository, 2023)
Linguistics is currently developing at a faster rate than any other scientific disciplines. Prior to the start of the 21st century, World linguistics addressed the text syntactically structurally, but analysis has subsequently intensified utilizing linguistic, linguistic, sociolinguistic, and psycholinguistic principles. They specifically acknowledge the time when linguocognitology emerged, which is determined by an individual’s cognitive activity. The definition of the term "cognitive" in cognitive linguistics is connected to the English word "cognitive - cognitive". This article will focus on linguistics, ideas and reflections on the concept of concept.